Religious Involvement, Moral Community and Social Ecology: New Considerations in the Study of Religion and Reentry - Stansfield, Richard (Journal of quantitative criminology, 2019)
To examine the link between an individual's religious involvement in prison and recidivism and assess how macro-level conditions in the counties to which individuals return shape this relationship.